2021
DOI: 10.1016/j.egycc.2020.100019
|View full text |Cite
|
Sign up to set email alerts
|

The ASEAN climate and energy paradox

Abstract: This article carries out a multisectoral qualitative analysis (MSQA) and policy integration analysis of six sectors important for climate mitigation in Southeast Asia in order to assess the status of the climate-energy nexus in the region. It concludes that Southeast Asia will be heavily affected by climate change but the mitigation efforts of the member states of the Association of Southeast Asian Nations (ASEAN) are incommensurate with the threat they face. Their nationally determined contributions under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 70 publications
(68 reference statements)
0
21
0
1
Order By: Relevance
“…Once again, wealthier countries tend to have better environmental performance as evidenced by the positive and significant coefficient of GDP. However, the effect is less pronounced than in Equation (2), where now a 1% increase in GDP per capita results in the environmental performance falling by 0.0261, holding other factors constant. Overall, a country tends to perform worse in terms of its environmental score if it belongs to the region of ASEAN, Greater Middle East, or Sub-Saharan Africa.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Once again, wealthier countries tend to have better environmental performance as evidenced by the positive and significant coefficient of GDP. However, the effect is less pronounced than in Equation (2), where now a 1% increase in GDP per capita results in the environmental performance falling by 0.0261, holding other factors constant. Overall, a country tends to perform worse in terms of its environmental score if it belongs to the region of ASEAN, Greater Middle East, or Sub-Saharan Africa.…”
Section: Resultsmentioning
confidence: 77%
“…In fact, Germanwatch has ranked three ASEAN countries among those that have suffered the greatest economic damage and number of fatalities from climate change [1]. Despite that, research has shown that the mitigation efforts of the Association of Southeast Asian Nations (ASEAN) have been insufficient to combat climate change [2]. This is worrying as estimates by the International Monetary Fund predict that climate change could decrease Southeast Asia's overall GDP by over 11% [3].…”
Section: Introductionmentioning
confidence: 99%
“…30 Tahun 2007 tentang Energi, PP No. 70 Tahun 2009 tentang Konservasi Energi, Instruksi Presiden dan beberapa peraturan menteri sebagai petunjuk operasionalnya [1] [2].…”
Section: Pendahuluanunclassified
“…Against this backdrop, the ASEAN member states have been enthusiastically embracing coal in recent years. As much of the world is pivoting away from fossil fuels, many Southeast Asian countries have been rapidly expanding their use of coal to meet the region's rising energy consumption, chiefly the projected rise in demand for electricity (Clark et al, 2020;Overland et al, 2021). In 2019, coal demand was projected to grow 5 per cent annually in Southeast Asia through 2023, the highest growth rate in the world.…”
Section: Coal In the Asean Countriesmentioning
confidence: 99%